VECTOR CONSTRUCTION STRATEGIES FOR TRANSFORMATION OF WHEAT PLANT - M. C. Baloglu; A. Battal; G. Aydin; A. Eroglu; M. T. Oz; M. Kavas; H. A. Oktem; M. Yucel (Journal of Animal and Plant Sciences, 2013)
Gene cloning and vector construction for plant genetic transformation are routine procedures in plant functional genomic studies. The availability of effective transformation vector is one of the pre-requisites for plant transformation studies. Here, we describe the construction of a series of transformation vectors through different genetic engineering techniques for wheat transformation. For this purpose, NAC-type transcription factor genes TaNAC69-1andTtNAM-B2 were isolated from T. aestivum and T. turgidum, respectively. Then they were cloned into different types of cloning and expression vectors. Besides traditional restriction enzyme digestion and ligation method, Gateway cloning technology which is a fast and reliable alternative cloning method were used for construction of wheat transformation vectors. The transformation vectors constructed in this study are suitable for use in both particle bombardment (biolistic) and Agrobacterium based transformation protocols for wheat plant.
Keywords: Traditional gene cloning; Gatewaygene cloning; Vector construction; Wheat transformation